The Destiny of Human Languages: Will they all Die? Sociolinguistic Investigation in Language Death and Revitalization - Amir Ibrahim Khudair (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In this essay the researcher focuses on language death, its internal and external causes in addition to its consequences on the speakers, cultures and knowledge as well. Then, he displays examples of American and European indigenous languages accompanied with the economic and political conditions within which these languages began retreating, declining and then dying out. The sorrowful point in this essay culminates when it deals with language suicide. This linguistic tragedy occurs when the speakers wittingly decide to leave their language under an illusory impression that their own native language is but an inferior one and they have to adopt another superior language due to economic and political interests. Finally, the mechanisms of revitalization of the dying and endangered languages are also investigated to create hope for the next generations to preserve our identity and our universal language and culture diversity.